Responses of buffel grass to different regrowth periods and residue heights (Research, Society and Development, 2020)
The objective was to evaluate the effect of the regrowth period and the residual height on the growth of buffel grass. A randomized block design was used, with three replications. The treatments consisted of four residue heights (20, 30, 40 and 50 cm) and four rest periods (15, 25, 35 and 45 days), in a 4x4 factorial arrangement. Dry matter and mineral content, grass production and productivity were determined. The data were submitted to regression analysis at 5% significance. There was no interaction between residue height and regrowth period for any of the variables. Productivity did not differ due to any of the sources of variation. The levels of mineral matter decreased linearly as a function of the regrowth period and the height of the residue, reaching 8.65 and 8.84% at 45 days and 50 cm in height, respectively. The forage production was better adjusted to linear equations according to the regrowth period, reaching averages of 8884.4 kg ha-1 of fresh mass and 2338.1 kg ha-1 of dry mass at 45 days. Buffel grass managed with 45 days of regrowth provided greater forage production per unit area. The shorter residue heights and the shorter regrowth periods provided higher concentrations of minerals in the forage.